The impact of FDI on Malaysia economic growth / Muhammad Azim Halizam - Halizam, Muhammad Azim (Faculty of Business and Management, 2020)
Malaysia has shown a remarkable progress in its economic growth in the past decade. However, the economic growth in Malaysia has cause foreign direct investment (FDI) volatile in the market. The main objective of this research is to analyse the impact of FDI on Malaysia economic growth proxied by real gross domestic product (GDP), foreign direct investment (FDI), gross fixed capital formation (DI), population growth (POP), and trade openness (TO). Analysis was done using Autoregressive Distributed Lag Model (ARDL) bound test approach with the period range of study was from 1970 until 2018. The empirical results also show with focus on FDI macroeconomic could improves the growth of economic and give a positive significant result in Malaysia. One policy recommendation is with the corporation from government agencies can enhance the economic growth and also can improve the stability in the economy.